HEALTHY SMART DOOR BASED ON BODY TEMPERATURE USING ARDUINO UNO AND FUZZY LOGIC - Fadhillah Azmi; Gopas Pasaribu; Rizki Imanuel (Sean Institute, 2021)
Since the end of 2019, the spread of Corona Virus Disease (COVID-19) has always shown an increase from time to time, this is due to the rise of physical contact, both directly between humans and through contact with equipment or public facilities. Automated public facilities and early detection of humans who have the potential to spread disease are effective ways to prevent physical contact between the spreader and other humans. Body temperature is one indicator that shows how the human body is and its ability to generate or reduce heat in the body. Based on the information obtained, the normal human temperature is in the range of 36.5-37.20C, whereas if it is above that temperature a person can be said to have a fever, where fever is a symptom of COVID-19. However, the human body temperature is also relatively fluctuating depending on activities and environmental conditions. For this reason, a method that makes it easier to analyze body temperature based on grouping is used, namely the fuzzy logic method which is implemented into the Arduino Uno microcontroller as an automatic control tool